Electrochemical behavior of AgCu50 in alkaline media in the presence of chlorides and 2-mercaptobenzothiazole - Grekulović V.; Rajčić-Vujasinović M.; Mitovski A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Electrochemical behavior of an alloy AgCu50, pure copper, and pure silver, respectively, was investigated by measuring the open circuit potentials using anodic potentiodynamic polarization and potentiostatic method in 0.1 moldm-3 NaOH + 0.02 moldm-3 NaCl solution, without and with adding 2-mercaptobenzothiazole in various concentrations (0.00001 - 0.001 moldm-3). Anodic polarization curves for AgCu50 alloy, showed four current peaks. Potentiostatic curves showed that values of the stationary current densities drop down with the increase of 2-mercaptobenzothiazole concentration in the electrolyte. The electrode surface was analyzed by optical microscopy after the potentiostatic oxidation. Micrographs confirmed that 2-mercaptobenzothiazole has got the inhibitory effect by forming the film of CuMBT and AgMBT which protect the electrode surface from corrosion. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. ON.172060]